Measure 11 Sentencing Reform in Oregon: Implementation and System Impact, 1990-1999 - Merritt, Nancy ([Verlag nicht ermittelbar], 2005)
This study explored the implementation and impact of Measure 11 (passed by Oregon voters in 1994), which imposed long mandatory prison terms for 16 designated violent and sex-related offenses, prohibited "earned time," and provided for mandatory waiver of youthful offenders to adult court. Measure 11 penalties were longer than those imposed under sentencing guidelines. Juveniles aged 15 years or older were also subject to the measure. The researchers addressed the implementation and impact of the measure on prosecution, sentencing, and convictions, both statewide and in three separate counties based on the Oregon Criminal Justice Commission (OCJC) data and the Oregon Department of Corrections (DOC) data. Variables include offender characteristics, plea trial information, number of convictions, prison term for convictions, severity of offense, M11-eligible and alternate offense, and description of most severe offense.